ASSESSMENT OF HISTOPATHOLOGICAL RESPONSE TO NEOADJUVANT CHEMORADIOTHERAPY IN GASTRIC CANCER PATIENTS: A MULTI-CENTER RANDOMIZED STUDY - V. Yu. Skoropad; S. G. Afanasyev; S. V. Gamayunov; P. V. Sokolov; Ye. S. Zhavoronkova; N. K. Silanteva; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал)
A multicenter randomized trial was conducted to assess histopathological response to neoadjuvant chemoradiotherapy in patients with locally advanced gastric cancer.Material and Methods. Patients of the study group received conformal radiation therapy (total dose of 46 Gr/23 fractions) with concurrent chemotherapy consisted of capecitabine at a dose of 1850 mg/m2 twice daily during the whole course of radiotherapy, and oxaliplatin at a dose of 85 mg/m2 on days 1 and 21. After an interval of 4–6 weeks and a control examination, in the absence of disease progression, patients were scheduled for surgery (gastrectomy or D2 subtotal gastric resection) and 4 cycles of adjuvant chemotherapy according to the FOLFOX4 or CAPOX regimens.Results.The study included 70 patients, including of 35 patients in the study group. Men predominated (n=23), the age ranged from 22 to 76 years (median – 61 years). The middle third of the stomach was the most common tumor location (n=19); involvement of the entire stomach occurred in 5 cases. Ulcerative and diffuse infiltrative forms were the most common (n=29). Well-and moderately-differentiated adenocarcinoma was observed in 11 patients and poorly – differentiated adenocarcinoma in 24 patients, including signet ring-cell cancer (n=8). In accordance with the clinical T, N and M categories, patients were distributed as follows: T3 – 22 patients, T4a/b – 13; N0 – 13, N1 – 12, N2–3 – 10; M0 – 35; stage IIB – 12, and stage III–IVA – 23 patients. Gastrectomy was performed in 30 patients and subtotal resection of the stomach in 4 patients; D2 lymphodissection was performed in all cases. One patient was not operated on due to disease progression. Of the 47 patients achieving pathological response, 5 (14.7%) patients had a complete pathological response. Among patients achieving pathological response, a statistically significant predominance of less advanced tumors was found (in accordance with the ypT category and stage).Conclusion. In general, a decrease in the pathological tumor stage compared to clinical stage was registered in 62 % of patients. Taking into account the data available in the world literature on high survival rates in patients with pathological complete regression, the optimization and implementation of neoadjuvant therapy techniques is of great importance.